2014
DOI: 10.1002/anie.201402501
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Protein Surface Sensors as a Tool for Analyzing Small Populations of Proteins in Biological Mixtures

Abstract: Optical cross-reactive sensor arrays (the so-called chemical "noses/tongues") have recently been demonstrated as a powerful tool for high-throughput protein detecting and analysis. Nevertheless, applying this technology to biomarker detection is complicated by the difficulty of non-selective sensors to operate in biological mixtures. Herein we demonstrate a step toward circumventing this limitation by using self-assembled fluorescent receptors consisting of two distinct recognition motifs: specific and non-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 55 publications
1
55
0
Order By: Relevance
“…The ability to selectively sense His-CaM's surfaceb yanonspecific synthetic receptor is in agreement with our previous studies, [12] showing that when as ynthetic agent is brought in the vicinity of ap rotein, it could preferentially interact with its surface. We therefore expected that even as mall sensor library, consisting of five different receptors (Figure 2, compounds 1-5)w ould be sufficient to identify as ensor that can respondt o surfaces of other His-tag-labeled proteins.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The ability to selectively sense His-CaM's surfaceb yanonspecific synthetic receptor is in agreement with our previous studies, [12] showing that when as ynthetic agent is brought in the vicinity of ap rotein, it could preferentially interact with its surface. We therefore expected that even as mall sensor library, consisting of five different receptors (Figure 2, compounds 1-5)w ould be sufficient to identify as ensor that can respondt o surfaces of other His-tag-labeled proteins.…”
Section: Resultssupporting
confidence: 92%
“…We have shown that when attached to selective protein binders, these receptors exhibit much higher affinity and selectivity toward the surfaces of their protein targets. [12] In this study,w e take this approach as tep furthera nd demonstrate how it can be used to create fluorescentm olecular sensors that respond to dynamic changes that occur on the surfaces of His-taglabeled proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that nucleic acid based ligand assemblies can be used to control protein activities. [13] These studies suggest it is feasible to design molecular scaffolds to optimize the geometry of receptor clustering mediated by Met-binding aptamers. Future studies along these lines would provide deeper insight to the design of more productive HGF mimetics.…”
mentioning
confidence: 99%
“…[1,8] Recently,o ptical sensorsh avee merged as ah ot research issueowing to theiradvantagesofsimpleoperation, excellent selectivity, high sensitivity, non-destructivity, andr eal-time analysis. [9][10][11][12][13] Yetd espite thes ignificant successesa chievedi n many analytes, [14][15][16][17][18][19] examplesofD 2 Oprobe arestill quiterare, andthe challenge lies in thesevereinterference from H 2 O. In fact,tothe best of ourknowledge,sofar therewereonlytwo reportso nm aterial-based D 2 Oo ptical sensors.…”
mentioning
confidence: 99%
“…[2] Currently,the widely used analytical methods for qualitative and quantitative detection of H 2 Ocontent in D 2 O are atomic absorption spectroscopy, [5] nuclear magnetic resonance spectroscopy, [6] and infrared laser spectroscopy, [3,7] yet they suffer from several drawbacks,s uch as non-portability,requirement of expensive instruments and specialized technicians,t ime-consuming nature,a nd complicated operations,l eading to inconvenience in rapid point-of-need detection. [9][10][11][12][13] Yetd espite thes ignificant successesa chievedi n many analytes, [14][15][16][17][18][19] examplesofD 2 Oprobe arestill quiterare, andthe challenge lies in thesevereinterference from H 2 O. [9][10][11][12][13] Yetd espite thes ignificant successesa chievedi n many analytes, [14][15][16][17][18][19] examplesofD 2 Oprobe arestill quiterare, andthe challenge lies in thesevereinterference from H 2 O.…”
mentioning
confidence: 99%